A molecular dynamics investigation of the atomic structural behavior of the interaction between amyloid beta protein and Aspirin within an aqueous nanodomain (vol. 146, pg. 851, 2023) - Le, Quynh Hoang; Heydaripour, Shokoufeh; Farhadi, Bita; Rashid, Rzgar Farooq; İnç, Mustafa (Elsevier Sci Ltd, 2026)
[Abstract Not Available]